DIAMOND FRAUD ANALYSIS IN DETECTING FINANCIAL STATEMENT FRAUD WITH THE AUDIT COMMITTEE AS MODERATING VARIABLE (Empirical Study on Sub Construction Companies listed on the IDX for the 2014-2018 period) - Rianto; Muhammad Irfan; Patriandari; Lisdawati (INQUISITIVE : International Journal of Economic, 2021)
The purpose of this study was to determine how much the influence of Fraud Diamond in detecting Financial Statement Fraud with audit committee variables as moderating variables in construction sector companies in 2016-2020, both partially and simultaneously. The research method used is hypothesis testing (hypothesis testing). Data collection techniques are carried out using secondary data types in the form of annual financial statements of construction sector companies on the Indonesia Stock Exchange during the 2016-2020 period. Data was collected using purposive sampling. The data analysis technique used in this study is the Moderated Regression Analysis (MRA) analysis. The results showed that the Nature of Industry had a positive effect on the Financial Statement Fraud on construction sector companies listed on the IDX, while the Financial Targets, Rationalization, and Capability did not affect the Financial Fraud statement on construction sector companies listed on the IDX. The research also shows that the audit committee as a moderator is not able to moderate the influence of the Nature of Industry and Capability on Financial Statement Fraud. whereas the Audit Committee as a moderator weakens the relationship of the Financial Targets to the Financial Statement Fraud, then the Audit Committee as a moderator can strengthen the relationship of the Rationalization of the Financial Statement Fraud.